Pengaruh Labelisasi Halal, Citra Merek, dan Kesadaran Halal terhadap Keputusan Pembelian Produk Makanan Kemasan Impor (Studi pada Mahasiswa di Kota Medan) - Salman Munthe (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
Consumer purchase decisions regarding imported packaged food products are an important aspect influenced by the interaction between global marketing appeal and adherence to religious values. This study aims to explore the influence of halal labeling, brand image, and halal awareness on the purchase decisions of imported packaged food products among university students in Medan. Utilizing a quantitative approach with a sample of 100 student respondents and applying multiple linear regression analysis, this study finds that halal labeling, brand image, and halal awareness partially and simultaneously have a significant impact on purchase decisions. The results indicate that brand image has the most dominant positive influence, highlighting the strong exposure of global trends and lifestyles among university students in the short term. However, the presence ofofficial halal labeling and high consumer halal awareness are also proven to have a significant influence, acting as crucial screening instruments in providing spiritual security and mitigating doubts regarding foreign products. This study also highlights the importance of credible halal certification and information transparency from manufacturers to minimize uncertainty in the imported product market and support the protection of Muslim consumers.